Lecturers’ Perspectives on Difficult Biology Education Courses in Nigerian Colleges of Education - Edidiong Emmanuel AKPAN (MASI Mandiri Edukasi, 2025)
The study examines lecturers’ perceptions of challenging courses in the Biology Education curriculum at colleges of Education in Southwest Nigeria. Using a descriptive survey method with 25 lecturers, data were collected through a validated questionnaire (r = 0.74). The results show that more female lecturers (57%) are compared to their male counterparts (43%). The findings also revealed that 14 lecturers held M.Ed./MSc (Ed), 6 had Ph.D., while 3 possessed B.Ed/BSc (Ed). The data further indicated that lecturers with 1 to 3 years and 4 to 6 years of experience were more numerous. The study identified 14 courses in the NCE Biology Education curriculum that lecturers found difficult. Courses such as Viruses, Bacteria, and Lower Plants (79.2%), Diversity of Chordates (78.2%), and Genetics (69.1%) were perceived as the most challenging. The research concludes that lecturers at the College of Education consider some courses they teach from NCE 1 to 3 as difficult. Recommendations include increased use of demonstrations to facilitate understanding of abstract concepts.